2011
DOI: 10.3945/ajcn.110.005611
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 fatty acid supplementation increases the rate of muscle protein synthesis in older adults: a randomized controlled trial

Abstract: Omega-3 fatty acids stimulate muscle protein synthesis in older adults and may be useful for the prevention and treatment of sarcopenia. This trial was registered at clinical trials.gov as NCT00794079.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
521
12
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(604 citation statements)
references
References 47 publications
26
521
12
12
Order By: Relevance
“…In a cross-sectional analysis of the of the InCHIANTI study [88] Abbatecola et al [138] reported that n-3 fatty acid concentrations were associated with a shorter time to complete a 7-m walk, independent of multiple confounders; at the 3-year follow-up, baseline n-3 fatty acid concentrations continued to be inversely associated with the development of impaired physical performance, as assessed by the SPPB (OR: 0.21; 95% CI: 0.08-0.53; p = 0.001) [138]. Smith et al [139] previously published novel evidence supporting the efficacy of n-3 fatty acid supplementation on its role in increasing muscle anabolic signalling activity and stimulating MPS above basal postabsorptive values in older adults. In a recently published RCT, Smith et al [140] further showed that a 6-month n-3 fatty acid intervention, without exercise, had statistical and clinically beneficial effects on attenuating sarcopenic symptomology by increasing thigh muscle volume (3.6%; 95% CI: 0.2-7.0%), hand-grip strength (2.3kg; 95% CI: 0.8-3.7kg) and upper/lower body 1-RM muscle strength (4.0%; 95% CI: 0.8-7.3%) (all p <0.05).…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional analysis of the of the InCHIANTI study [88] Abbatecola et al [138] reported that n-3 fatty acid concentrations were associated with a shorter time to complete a 7-m walk, independent of multiple confounders; at the 3-year follow-up, baseline n-3 fatty acid concentrations continued to be inversely associated with the development of impaired physical performance, as assessed by the SPPB (OR: 0.21; 95% CI: 0.08-0.53; p = 0.001) [138]. Smith et al [139] previously published novel evidence supporting the efficacy of n-3 fatty acid supplementation on its role in increasing muscle anabolic signalling activity and stimulating MPS above basal postabsorptive values in older adults. In a recently published RCT, Smith et al [140] further showed that a 6-month n-3 fatty acid intervention, without exercise, had statistical and clinically beneficial effects on attenuating sarcopenic symptomology by increasing thigh muscle volume (3.6%; 95% CI: 0.2-7.0%), hand-grip strength (2.3kg; 95% CI: 0.8-3.7kg) and upper/lower body 1-RM muscle strength (4.0%; 95% CI: 0.8-7.3%) (all p <0.05).…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%
“…Despite the exact mechanisms being unclear, the investigators of these studies identified that the anabolic effects of n-3 fatty acids are independent of any significant influence on inflammation. Rather, they likely involve alterations in both anabolic and catabolic pathways, improved mitochondrial functioning and biogenesis, neuroprotection and motor-neuron excitability properties [139][140][141].…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%
“…Recent human studies have found that supplementation with long chain n-3 PUFA increases rates of protein synthesis and augments the muscle protein anabolic response, and may also attenuate acute muscle loss (cachexia) (236)(237)(238)(239)(240)(241) . One small observational study found a negative association with appendicular lean mass and saturated fat, and a comprehensive study of dietary fat composition and muscle mass found positive associations with the PUFA:SFA ratio and negative associations with saturated and trans fatty acids (15,81) .…”
Section: Dietary Fat Compositionmentioning
confidence: 99%
“…Among those, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) also have direct muscle anabolic actions independent of their anti-inflammatory actions (4-6) suggesting that this might be a valuable therapeutic approach for the treatment of PEW in MHD patients (4,7). In this study, we aimed to estimate the association between high-dose v-3 fatty acid supplementation on the rates of muscle protein synthesis and breakdown in MHD patients with underlying systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%